Handbook of Materials for Nanomedicine Polymeric Nanomaterials. - Torchilin, V. P. (Milton : Pan Stanford Publishing, 2020)
In the fast-developing field of nanomedicine, a broad variety of materials have been used for the development of advanced delivery systems for drugs, genes, and diagnostic agents. With the recent breakthroughs in the field, we are witnessing a new age of disease management, which is governed by precise regulation of dosage and delivery. This book presents the advances in the use of lipid-based and inorganic nanomaterials for medical imaging, diagnosis, theranostics, and drug delivery. The materials discussed include liposome-scaffold systems, elastic liposomes, targeted liposomes, solid lipid nanoparticles, lipoproteins, exosomes, porous inorganic nanomaterials, silica nanoparticles, and inorganic nanohybrids. The book provides all available information about them and describes in detail their advantages and disadvantages and the areas where they could be utilized successfully.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Nanostructures; MEDICAL / Pharmacy; Nanomedicine -- Handbooks, manuals, etc; Nanotechnology -- Health aspects -- Handbooks, manuals, etc